Process synthesis and optimization of syngas and ammonia production in nitrogen fertilizers complexes: energy, energy integration and CO2 emissions assessment. - Flórez-Orrego, Daniel Alexander (2018)
The primary aim of this thesis is to propose a method to develop the process synthesis and optimization of the production of syngas and ammonia, as well as other byproducts such as marketable CO2, in synthetic nitrogen fertilizers (SNF) complexes. The baseline analysis relies on a typical 1000 t/day ammonia production plant composed of syngas production, purification (CO2 capture) and compression systems, along with an industrial ammonia synthesis unit. Initially, exergy and exergoeconomy analyses are used to identify the most important sources of energy consumption and irreversibility associated to the operation units of the integrated plant. From these results, a variety of alternatives for the improvement of the performance at the plantwide and component level are thoroughly examined along the different chapters. Due to the large amount of possible configurations and interrelations, the optimization process may become a formidable engineering task to be solved by using merely trial and error approaches. Accordingly, a systematic approach, based on the combination of heuristics, thermodynamic principles and mathematical programming is used to identify, evaluate, and determine the best configurations in terms of exergy consumption, degree of energy integration, process irreversibility, atmospheric CO2 emissions and operating costs. In this way, the process synthesis and optimization include not only the modification of the main process parameters but also the arrangement of the chemical plant components, suitably integrated to the waste heat recovery and cogeneration systems. Several aspects concerning: (i) the choice of the syngas purification system, (ii) the nature of the energy resources consumed, (iii) the exploitation of the thermodynamic potential at higher temperatures, (iv) the increase of the pre-combustion carbon capture by introducing chemically recuperated concepts, (v) the gradual variation of operating conditions by applying Le Châtelier and Counteraction principles, as well as (vi) the environmental benefits of using alternative energy sources to decarbonize the SNF sector are analyzed in the light of the reduced room of improvement found in modern conventional ammonia production facilities. The results show significant potentials for decreasing the exergy intensity and environmental impact of those facilities. This allows issuing relevant recommendations for revamping the existing plants or embracing new approaches that attempt to minimize the economic costs, the process inefficiencies and mitigate the environmental impact produced. An efficiency increase of about 8-10% can be achieved by using more efficient combined cycle cogeneration systems with an affordable marginal investment cost. Alternative configurations with enhanced pre-combustion carbon capture, using either a CRGT system or upgraded biomass residues, may help cutting down the overall CO2 emissions in the syngas production in 20-28% or even promoting the decarbonization of the SNF sector at net rates of atmospheric CO2 depletion close to -2.3 tCO2/tNH3, respectively. The reduction of the process irreversibility has been also reduced by 10-13% in an industrial ammonia synthesis unit through the application of dual pressure systems and the introduction of a purge gas treatment process.